Effect of Hall Current on Unsteady Magneto Hydrodynamic Flow Past an Exponentially Accelerated Inclined Plate with Variable Temperature and Mass Diffusion (MATEMATIKA, 2018)
The present study is carried out to examine the effect of Hall current on unsteady flow of a viscous, incompressible and electrically conducting fluid past an exponentially accelerated inclined plate with variable wall temperature and mass diffusion in the presence of transversely applied uniform magnetic field. The plate temperature and the concentration level near the plate increase linearly with time. The governing equations involved in the present analysis are solved by the Laplace-transform technique. The velocity profile is discussed with the help of graphs drawn for different parameters like thermal Grashof number, mass Grashof number, Prandtl number, Hall current parameter, acceleration parameter, the magnetic field parameter and Schmidt number, and the numerical values of skin-friction have been tabulated. It is observed that the flow pattern is affected significantly with plate acceleration, Hall current. The importance of the problem can be seen in cooling of electronic components of a nuclear reactor, bed thermal storage and heat sink in the turbine blades.